On human rights - Griffin, James, 1933- (Oxford : Oxford University Press, 2010)
James Griffin's theory of the foundations of human rights offers answers as to what a human right is, how we can recognise one and how we can resolve the conflicts between different ones.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Human rights; Human rights -- Philosophy